2003
DOI: 10.2172/895654
|View full text |Cite
|
Sign up to set email alerts
|

NOx Control Options and Integration for US Coal Fired Boilers

Abstract: This is the fourteenth Quarterly Technical Report for DOE Cooperative Agreement No: DE-FC26-00NT40753. The goal of the project is to develop cost effective analysis tools and techniques for demonstrating and evaluating low NO x control strategies and their possible impact on boiler performance for boilers firing US coals. The Electric Power Research Institute (EPRI) is providing co-funding for this program. Using the initial CFD baseline modeling of the Gavin Station and the plant corrosion maps, six boiler lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The technology of injecting reagents into the fuel-rich zone for NO x reduction has been first applied to utility boilers by the REI Company in the United States, where the technology was called rich reagent injection (RRI). 27 − 29 Based on the test of two existing cyclone-fired utility boilers equipped with over-fire air (OFA), that is, a single wall-fired 130 MW unit (B.L. England Unit 1) and an opposed wall-fired 500 MW unit (Sioux Unit 1), RRI was demonstrated to achieve 30% NO x reduction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The technology of injecting reagents into the fuel-rich zone for NO x reduction has been first applied to utility boilers by the REI Company in the United States, where the technology was called rich reagent injection (RRI). 27 − 29 Based on the test of two existing cyclone-fired utility boilers equipped with over-fire air (OFA), that is, a single wall-fired 130 MW unit (B.L. England Unit 1) and an opposed wall-fired 500 MW unit (Sioux Unit 1), RRI was demonstrated to achieve 30% NO x reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Through the establishment of a mechanistic model of the ammonia-injected denitrification in a high-temperature reduction zone, Lu et al found that the reaction temperature window of NO x reduction with an NH 3 reagent injected at high temperatures was from 1200 to 1600 °C and the O 2 concentration in the flow gas should be less than 1 vol %. The technology of injecting reagents into the fuel-rich zone for NO x reduction has been first applied to utility boilers by the REI Company in the United States, where the technology was called rich reagent injection (RRI). Based on the test of two existing cyclone-fired utility boilers equipped with over-fire air (OFA), that is, a single wall-fired 130 MW unit (B.L. England Unit 1) and an opposed wall-fired 500 MW unit (Sioux Unit 1), RRI was demonstrated to achieve 30% NO x reduction.…”
Section: Introductionmentioning
confidence: 99%